Understanding Emotional Display Rules at Work and Outside of Work: The Effects of Country and Gender - MORAN, Christina M. (Institutional Knowledge at Singapore Management University, 2013)
This study examined the long-held, but empirically untested assumption that emotional display rules at work are different from more general display rules. We examined whether the effect of context (work vs. non-work) on display rules depended on rater gender, rater country (i.e.,Singapore, United States), and discrete emotion (anger, contempt, disgust, fear, sadness, and happiness). Results revealed that display rules at work involved less expressivity of emotion than did display rules outside of work for all six emotions. Further, display rules in Singapore involved less expressivity of anger, sadness, and fear than display rules in the US, with no country differences being observed for the emotions of happiness, contempt, and disgust. These results were qualified by significant country-by-gender interactions for anger, contempt, and disgust, a significant country by- context interaction for fear, and a three-way interaction (i.e., country-by-gender-by-context) for sadness.